Development of asnaf locator mobile application (ALMA) for Lembaga Zakat Selangor using Lean-Kanban method / Mohamad Zulridzwan Mohamad Basiran - Mohamad Basiran, Mohamad Zulridzwan (2015)
This project tries to propose a solution to the problems encountered by Lembaga Zakat Selangor (LZS) in identifying the eligible recipient of zakat funds. Lembaga Zakat Selangor is the authority in the state of Selangor responsible to collect alms from the people of Selangor and distribute the funds to the needy and other eligible recipients according to the Islamic Sharia law. There are many problems proposed by other researchers regarding people that are supposed to receive help from LZS but did not receive it due the miscommunications of information. The researcher tried to utilize the recent popular adoption of mobile application and crowdsourcing technology to solve this problem. Mobile application promises huge potential to improving people's lives supported by ubiquitous broadband internet connections. This project shall produce an application that allows the user to record the problems and locations of people in need of assistance especially from LZS so the institution can take actions to alleviate the difficult situations. In addition, the recent trend in software development is the gaining support of Agile and Lean software development methodologies. This research shall demonstrate the use of the combination of Lean and Agile using Kanban for mobile application development. The methodology is using the best practices suggested by other researchers for Lean Software Development combined with the use of Kanban board. This methodology is known as Lean-Kanban.